Atlas of Non-Gynecologic Cytology (Atlas of Anatomic Pathology,, 2018)
This text focuses on all aspects of non-gynecologic cytopathology, from key features of benign and malignant lesions, to diagnostic pearls and ancillary testing. Although this book is written by multiple authors, all chapters follow a similar format: brief introduction of the specific organ/system (including types of specimens and techniques to obtain samples), description of normal findings, and a practical approach to diagnose benign and malignant lesions. Key cytomorphological features, current terminology and molecular diagnostic tests are also highlighted within this volume. The Atlas of Non-Gynecologic Cytology is a practical resource for cytotechnologists, cytopathologists, and pathologists who are practicing general surgical pathology and cytopathology. The book is also a valued text for medical students, residents, fellows, and other allied health personnel who take care and/or treat patients based on the histological diagnosis of diseases.